PSEUDOEPITHELIOMATOUS HYPERPLASIA: A CASE REPORT - Dr Manish Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Pseudoepitheliomatous hyperplasia (PEH) is a benign epithelial proliferation that often mimics squamous cell carcinoma (SCC), posing a diagnostic challenge for clinicians. This case report highlights the importance of biopsy in distinguishing PEH from malignancy and presents the successful surgical management of a PEH lesion using a buccal fat pad flap. The case underscores the role of compliance in wound healing and demonstrates the clinical utility of the buccal fat pad in oral reconstruction, particularly in medically compromised patients.